Sharing Powers Among Indian Federalism - Bhat, Mohd Shafi (International Journal of Law Policy and Governance, 2024)
The Constitution of India has provisions for sharing powers among different units of governments situated in a vertical order, the Union, the State governments and the local governments. The scope and limits of powers of each of these units of governments is defined in terms of federalism and decentralization. The basic provisions regarding the distribution of powers between the Central and Provincial (state) governments are present in Part XI (Article 246) of the Constitution of India. The Constituent Assembly followed the system of division of powers as was envisaged in the Government of India Act of 1935 regarding the provisions about division of power in India. The items that can be legislated by the Union government, the State governments and jointly both by the Union government and State governments are mentioned in the lists known as List I- Union List, List II- State List and List III- Concurrent List. The present paper is an attempt to unravel the constitutional model of federal arrangements as networks of relationships weaved around and running across three points, Centre, State and institutions of local- self government. It is hereby argued that Constitution of India does provide for the Union having exclusive and special relationship with some states with a view to promote and to accommodate ethno- cultural perspective